(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
With the FDA’s clearance of Spritam, the first 3D printed tablet, precedent has been established for the use of 3D printing in the manufacture of drug delivery systems. Complex compositions and geometries may be prepared thanks to the ability to accurately dispense small quantities, fine spatial control, and layer-by-layer assembly. Because of the great degree of flexibility and control offered by 3D printing, dosage forms including numerous active medicinal components with complicated and customized release profiles may be created. This technology has a one-of-a-kind potential to prepare customized dosages to meet the requirements of specific patients. This study will focus on the 3D printing technologies that are being used to fabricate drug delivery systems, as well as the formulation and processing factors that must be taken into account. This essay will also provide an overview of the many dosage forms that have been created utilizing these technologies in the past ten years.